1995
DOI: 10.12968/bjom.1995.3.9.487
|View full text |Cite
|
Sign up to set email alerts
|

Survey of computerised midwifery information systems

Abstract: Exploring computerized midwifery information systems across the country and focusing on a research project and local initiatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Although computerised maternity information systems are supposed to make it easier to record and use data,17 many problems persist 18 19. Eleven of the trusts in our survey reported that it would take two or more weeks to obtain data that were not immediately accessible Unless information is readily available it cannot be used effectively to inform NHS decision making 1 6 9…”
Section: Discussionmentioning
confidence: 96%
“…Although computerised maternity information systems are supposed to make it easier to record and use data,17 many problems persist 18 19. Eleven of the trusts in our survey reported that it would take two or more weeks to obtain data that were not immediately accessible Unless information is readily available it cannot be used effectively to inform NHS decision making 1 6 9…”
Section: Discussionmentioning
confidence: 96%
“…While doctors and midwifery managers may have some power to shape EPR developments, the structural position of the practising midwife is somewhat different. A survey of computerization in the maternity services undertaken in the mid-1990s by Dobson (1995) found that although midwives were the main users of the systems being implemented, in nearly half of all maternity units surveyed midwives were not consulted about either their information needs or their choice of system. This resulted in the under-use of systems that midwives simply didn't feel they had any stake in.…”
Section: The Articulation Of Gender In Epr Systems Development: Discourse and Practicementioning
confidence: 99%
“…Similarly a UK review of midwifery systems showed a probable increase as [18] reported that 38% of obstetric units had maternity systems, and [3] showed 59% of 218 obstetric units had a maternity system, which is probably an increase over the two previous years. (This allows for different methodologies, as the interest of the former was in medicine rather than midwifery.…”
Section: Computerized Nursing Systemsmentioning
confidence: 99%
“…One advantage of distributed networked systems is that the users may be permitted to take local ownership of information, maintaining and accessing information determined relevant and useful as part of a coherent larger system. Dobson [3] looked at the presence and perceived usefulness of maternity systems. Forty per cent of respondents were not satisfied with their systems, and these were more concentrated in systems that had been customized for maternity use, rather than built specifically for the task.…”
Section: Introductionmentioning
confidence: 99%